Noncoding RNA Gas5 Is a Growth Arrest and Starvation-Associated Repressor of the Glucocorticoid Receptor - Kino, Tomoshige (2010)
The availability of nutrients influences cellular growth and survival by affecting gene transcription. Glucocorticoids also influence gene transcription and have diverse activities on cell growth, energy expenditure, and survival. We found that the growth arrest-specific 5 (Gas5) noncoding RNA, which is abundant in cells whose growth has been arrested due to lack of nutrients or growth factors, sensitized cells to apoptosis by suppressing glucocorticoid-mediated induction of several responsive genes, including the one encoding cellular inhibitor of apoptosis 2. Gas5 bound to the DNA-binding domain of the glucocorticoid receptor (GR) by acting as a decoy “glucocorticoid response element (GRE)”, thus, competing with DNA GREs for binding to the GR. We conclude that Gas5 is a ribo-repressor of the GR, influencing cell survival and metabolic activities during starvation by modulating the transcriptional activity of the GR.